Potential regulatory factors in the pathogenesis of ankylosing spondylitis - Liu, Hongxi; Zhou, Jun; Bi, Junwei; Yang, Wenbo (Cellular and Molecular Biology, 2020)
Ankylosing spondylitis (AS) is a chronic rheumatic disease that mainly affects the spinal joints (vertebrae). Spondylitis means inflammation of the spine, and ankylosing spondylitis means that bones tend to fuse. The AS causes the vertebrae to swell in the spine. Therefore, based on protein interaction network analysis, we conducted in-depth research on the molecular mechanism of key regulatory factors in the AS disease process. We carried out a differential analysis of the expression of miRNAs in disease samples and miRNAs in normal samples. Protein network interaction analysis is performed according to a group of target genes regulated by significant differentially expressed miRNAs and clustered into an interaction module. In addition, enrichment analysis of functions and pathways was performed on these modular genes. Based on the predictive analysis of multidimensional regulators, we identified a range of regulatory factors that have potential regulatory effects on AS, such as endogenous genes and transcription factors. We obtained 20 differentially expressed miRNAs and 7082 target genes and clustered into 11 modules. Enrichment results showed that these modular genes are mainly involved in the functions and pathways of protein polyubiquitination, neutrophil activation involved in immune response, and Wnt signaling pathway. We revealed ten transcription factors (MYC, NFKB1, and TP53). After network connectivity analysis, we obtained 12 internal drive genes (UBE2D1, CCNF, and NEDD4). These core genes are thought to be potential regulators of AS. MYC is also considered to be a core factor that inhibits SART3 phosphorylation and plays a vital role in the immunological pathogenesis of AS. The combination of the above analysis results can provide a new idea for biologists and medical scientists to study the immune pathogenesis of AS and can provide a valuable reference for subsequent treatment options.